1989 in European Vernacular Memory. (August 2017) - Breuer, Lars; Delius, Anna
This article is part of the special section titled The Genealogies of Memory, guest edited by Ferenc Laczó and Joanna Wawrzyniak In our contribution, we examine the vernacular memory of the end of Communism and the year 1989 in Europe. Analyzing sixteen focus groups conducted in Germany, Poland, Spain, and the United Kingdom, we concentrate on the question whether the events related to 1989 might have the disposition to become a transnational European lieu de mémoire . We show that 1989 is not a salient historical event for British and Spanish participants, while Polish and German respondents do connect it with patterns of national identity building. Differences between vernacular and official memories could be revealed as respondents hardly mentioned the democratic achievements made in the course of the transitions. A transnational dimension was only found in Poland, where respondents articulate a feeling of neglect toward their own national history. The Solidarity movement is being interpreted as a motor of liberation and Europeanization of Poland and as a pioneer of democratization on a European scale. German respondents remain in their national frame, focusing on flashbulb memories of the fall of the Berlin Wall and the issue of social integration of East and West Germany after 1990, which they evaluate as imperfect. The strong national bias of Polish and German focus groups raises doubts as to whether 1989 can become a transnational basis for a shared European memory.